Strategi Ketahanan Pangan di Masa Pandemi Covid-19: Penguatan Potensi Desa Melalui Sustainable Farming di Indonesia - Tasya Adhila Amalia; Jordan Aria Adibrata; Riko Ratna Setiawan (Hasanuddin University, 2022)
This paper aims to explain how the government should be able to optimize the village sector from a policy perspective in order to achieve sovereignty in the agricultural sector, and make it an alternative strategy of high significance during a pandemic. This is because so far the village has not become the main actor in achieving national food security, even though this sector has various potentials that can be developed through the principle of sustainable farming. This paper uses descriptive-qualitative methods using secondary data sources through literature and documentation studies. Various approaches such as the concept of Food Security, Securities Theory, and the concept of Decision Making as an analytical tool in studying the phenomena raised. As a result, the case study of the use of the Peatland Project (PLG) in the Food Estate program in the era of the Joko Widodo administration is a form of inefficiency because it has to go through a long process so that optimal results will only make Indonesia slow to prepare to face the world food crisis. Optimizing villages with the empowerment of the crop rotation method can provide significant changes in strengthening food through quality production and can reduce Indonesia's dependence on imports. This certainly shows that sustainable farming through village optimization can improve community welfare.